2015
DOI: 10.1007/s40881-015-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Learning through passive participation in asset market bubbles

Abstract: We report a laboratory experiment that investigates the impact of passive participation on bubble formation in asset markets with inexperienced and experienced traders. Some treatments employ pre-market training in which each participant is 'matched' with a trader from a different prior market and observes all trading details but does not directly participate in trading. We find that passive participation, similar to direct experience, significantly reduces mispricing in subsequent markets. This finding sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We find that by manipulating the price chart such that the price is displayed at the upper end of the scale, overvaluation can be altered by more than 30 percentage points. Thus, we demonstrate that in a bubble-prone experimental asset market with a constant —similar to what Huber and Kirchler (2012), Baghestanian and Walker (2015), and Cason and Samek (2015), among others, have shown for markets with a decreasing —seemingly irrelevant design choices can considerably affect market prices. In contrast, we do not find evidence of a change in price efficiency when manipulating the price chart in the opposite direction.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We find that by manipulating the price chart such that the price is displayed at the upper end of the scale, overvaluation can be altered by more than 30 percentage points. Thus, we demonstrate that in a bubble-prone experimental asset market with a constant —similar to what Huber and Kirchler (2012), Baghestanian and Walker (2015), and Cason and Samek (2015), among others, have shown for markets with a decreasing —seemingly irrelevant design choices can considerably affect market prices. In contrast, we do not find evidence of a change in price efficiency when manipulating the price chart in the opposite direction.…”
Section: Discussionsupporting
confidence: 80%
“…Tufte 1983; Beattie and Jones 1992), there is also evidence that in market settings already a different presentation of trading prices and the prior to the experiment can influence experimental results. Cason and Samek (2015) for example find that the visual representation of trading prices—either displayed in a column of text or in a graphical display—leads to significantly different price levels. Huber and Kirchler (2012) demonstrate that bubble formation is significantly reduced when the process is displayed in a graph instead of a table prior to the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Cason and Samek (2015) contains an example of results that switch to being significant under the alternative measurement variation. Part of this study compares markets in which information is shown to inexperienced traders as either text (T extM 1) or graphically (V isualM 1).…”
Section: Original Vs Suggested Mispricingmentioning
confidence: 99%
“…This study begins to fill this gap by analyzing three types of graphic displays to determine the extent to which each type of display regarding NPS pollution motivates pollution abatement. One prior study, Cason and Samek (), used an economic experiment to analyze the impacts of using data visualization tools in asset market bubbles. Though not related to NPS pollution, the study used an experimental design similar to ours involving exposing subjects to different types of information displays.…”
Section: Introductionmentioning
confidence: 99%